Evaluating User Satisfaction and Educational Impact of the Sorghum Entrepreneur Marketplace: An Application of the Pieces Framework - Noerhartati, Endang; Saurina, Nia; Idris, Azlina (Research Horizon, 2023)
This study explores the pivotal role of digital marketplaces in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a focus on the sorghum entrepreneur marketplace. Through a comprehensive methodological approach that includes interviews, observations, literature reviews, and system design analysis via use case diagrams, this research investigates the user satisfaction levels of the marketplace employing the Performance, Information, Economy, Control, Efficiency, and Service (PIECES) framework. The findings reveal an average satisfaction level of 4.41 across these indicators, indicating a high degree of user satisfaction with the marketplace. This study extends beyond traditional marketplace evaluation to consider the educational implications of digital platforms in promoting agricultural entrepreneurship. It highlights the marketplace's role not only as a commercial tool but also as an educational resource that enhances users' digital literacy, e-commerce understanding, and sustainable agricultural practices. This dual focus underscores the importance of integrating educational objectives into digital marketplace development, aiming to foster lifelong learning and professional growth among users.